Vitamin E Extraction from Magnesium Salts of Palm Fatty Acid Distillates - Dianika Lestari; Khalisa Putri Aqilah; Salsafia Putri; Ardiyan Harimawan; Diky Mudhakir; Muhamad Insanu (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
This research studied how the type of organic solvent and the number of extraction stages affect the vitamin E cumulative extraction yield and recovery rate from Mg-PFAD. First, PFAD was saponified to produce Mg-PFAD, then vitamin E was extracted from the Mg-PFAD using ethanol, isopropanol, or hexane, followed by evaporation to produce vitamin E concentrate. Three-stage hexane extraction with a solvent to Mg-PFAD mass ratio of 3 kg solvent/kg Mg-PFAD produced the highest vitamin E recovery rate. Organic solvent with a lower polarity gave a higher extraction yield and recovery rate of vitamin E from Mg-PFAD. In general, an increase of the number of extraction stages led to an increase of the vitamin E extraction yield and recovery rate from Mg-PFAD.